Association between oral health and quality of life among primary school students in Hue city, Vietnam - Nguyen, Thi Nhat Vy; Nguyen, Gia Kieu Ngan (Tạp chí Y Dược Huế, 2026)
Background: Oral health problems, especially dental caries, remain highly prevalent among children and reduce quality of life. Objectives: This study assessed oral health status and oral health-related quality of life (OHRQoL) among Vietnamese primary school children and examined its associations with clinical factors. Materials and method: A cross-sectional study was conducted among 343 children aged 8-11 years at a Hue City elementary school. Participants completed the Child Perceptions Questionnaire (CPQ) to evaluate OHRQoL across four domains: oral symptoms, functional limitations, emotional well-being, and social well-being. Clinical examinations measured dental caries (DT+dt), missing teeth (MT+mt), and oral hygiene (OHI-S). Data were analyzed using descriptive statistics, t-tests, ANOVA, and multivariate linear regression. Results: The sample comprised 180 females (52.5%) and 163 males (47.5%). Mean DT+dt was 6.5 ± 3.9, MT+mt 0.2 ± 0.6, and OHI-S 1.5 ± 0.7. The total CPQ score was 13.6 ± 11.9, with no significant gender differences but increasing scores with age (significant in emotional well-being, p = 0.042). Regression analysis showed DT+dt (β = 0.50, p < 0.01), MT+mt (β = 2.54, p < 0.05), and OHI-S (β = 2.75, p < 0.01) as significantly associated with total CPQ scores, with domain-specific effects strongest in emotional and social well-being. Conclusion: Clinical oral health factors are strongly associated with OHRQoL among Vietnamese primary school children, particularly a high burden of untreated dental caries and poor oral hygiene.